Dual-Band Shared-Aperture Antenna with Pattern and Polarization Diversity - Jia Cheng; Tianyu Gao; Dongpeng Han; Changfei Zhou (Applied Sciences)
This paper proposes a dual-band co-aperture antenna, which covers 2.09–11.61 GHz (9.52 GHz, 138.9%) and 21.6–29.6 GHz (8 GHz, 31%). The overall size of the proposed antenna is 0.76 × 0.76 × 0.37 λ03, where λ0 is the free space wavelength of the lowest operating frequency of 2.09 GHz. By removing the internal metal of the monopole antenna and adding a Vivaldi antenna at the bottom of the bowl monopole antenna, dual-band radiation characteristics can be achieved. A medium polarization converter is used to achieve circular polarization and improve the broadside gain in the high-frequency band. The simulation results show that the antenna has a stable omnidirectional radiation pattern in the low-frequency band and a directional radiation pattern in the high-frequency band.